2021
DOI: 10.3390/md19120677
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids from the Brown Alga Rugulopteryx okamurae and Their Anti-Inflammatory Activity

Abstract: Brown algae of the Family Dictyotaceae produce an array of structurally diverse terpenoids, whose biomedical potential in the anti-inflammatory area has been scarcely explored. Herein, the chemical study of the alga Rugulopteryx okamurae has led to the isolation of ten new diterpenoids: rugukadiol A (1), rugukamurals A–C (2–4), and ruguloptones A–F (6–10). The structures of the new compounds were established by spectroscopic means. Compound 1 exhibits an unprecedented diterpenoid skeleton featuring a bridged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…It is widely reported that algal species are good sources of fibre, various vitamins, minerals, and that several algal derived bioactives have anti-inflammatory properties when tested in models of inflammation (Lee et al 2017;Ismail et al 2020;Alkhalaf 2021;Cuevas et al 2021;Chen et al 2022;Mihindukulasooriya et al 2022). These beneficial properties have spawned growth in the algal food production industry and algal products are largely good for health.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that algal species are good sources of fibre, various vitamins, minerals, and that several algal derived bioactives have anti-inflammatory properties when tested in models of inflammation (Lee et al 2017;Ismail et al 2020;Alkhalaf 2021;Cuevas et al 2021;Chen et al 2022;Mihindukulasooriya et al 2022). These beneficial properties have spawned growth in the algal food production industry and algal products are largely good for health.…”
Section: Discussionmentioning
confidence: 99%
“…Most of those address its use as biomass for anaerobic co-digestion, composting and biofertilizer production, and the development of bio-based plastic materials (bioplastics). Additionally, potential anti-inflammatory and antimicrobial activities have been suggested, as well as the ability to inhibit -glucosidase, which may be attractive features for the biomedical, pharmaceutical or food industries [ 12 ].…”
Section: Applicationsmentioning
confidence: 99%
“…The search for new anti-inflammatory agents is of great relevance to the medical field since inflammation is associated with several difficult to treat diseases, such as some types of cancer, rheumatoid arthritis, inflammatory bowel disease and diabetes [ 12 ].…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations